Perbandingan Pengolesan Edible Coating Terhadap Ketahanan Warna Basis Resin Akrilik Gigi Tiruan - Putra, Rindra Aji Widhiya, drg. Noor Hafida Widyastuti, Sp.KG, drg. Nilasary Rochmanita S, MDSc (2015)
crylic resin (Polymethyl Methacrylate) is used as the base material on the denture. Acrylic resin as a base material has the disadvantage which can absorb oral fluids that can cause discoloration. Prevention of absorption of oral fluids that can affect the durability of color in acrylic resin base can be overcame by applying edible coating. Edible coatings are food coatings that can be consumed by products overlaid. The purpose of this study was to determine colour durabilits differences in acrylic resin base which was coated by edible coating and not coated. This study was an experimental research laboratory. The study used 32 samples of heat cured acrylic resin shaped plate with a size of 20 mm x 20mm x 2mm samples were divided into two groups. The first group was coated by edible coating and the second group was not coated by edible coating. Furthermore, the two groups were immersed in the colored liquid for 18 days and measured wave numbers of two groups ware measured by FTIR spectrophotometer instrument. The result of the Independent Sample T-Test showed the value of P = 0.000 (P <0.000). So it can be concluded that there was a difference in color between acrylic resin base which was smeared by edible coating and not coated